Joint Effect of Central Obesity and Family History on Hypertension in Type 2 Diabetes: A Cross-Sectional Study in China - Chen X; Chen L; Hu R; Yao W; Ma Z; Zhong J (Diabetes, Metabolic Syndrome and Obesity)
Xiangyu Chen, Lijin Chen, Ruying Hu, Weiyuan Yao, Zhimin Ma, Jieming Zhong Department of Non-Communicable Disease Control and Prevention, Zhejiang Provincial Center for Disease Control and Prevention, Hangzhou, Zhejiang, 310051, People’s Republic of ChinaCorrespondence: Jieming Zhong, Department of Non-Communicable Disease Control and Prevention, Zhejiang Provincial Center for Disease Control and Prevention, Hangzhou, Zhejiang, 310051, People’s Republic of China, Tel +86 571 87115159, Email jmzhong@cdc.zj.cnPurpose: This study aimed to examine the joint effect of central obesity (CO) and family history of hypertension (FHH) on hypertension in Chinese patients with type 2 diabetes mellitus (T2DM).Methods: A total of 1756 T2DM patients were enrolled from a cross-sectional study conducted in Zhejiang Province, China (March - November 2018). Multivariate logistic regression models were used to analyze factors associated with hypertension and to assess CO-FHH interactions on both additive and multiplicative scales. Associations between waist circumference (WC) and systolic/diastolic blood pressure (SBP/DBP) were evaluated using generalized additive models (GAM) and Spearman correlation. The relationship between WC and hypertension was further explored using restricted cubic splines (RCS).Results: The prevalence of hypertension was 64.52%. WC was positively correlated with SBP (r = 0.25, P< 0.001) and DBP (r=0.27, P< 0.001), and showed a linear association with hypertension in both sexes (P for non-linearity> 0.05). After adjusting for potential covariates, T2DM patients with both CO and FHH had a 4.64-fold higher risk of hypertension (95% CI: 3.22– 6.67) compared to the reference group. A statistically significant additive interaction between CO and FHH was observed, with a relative excess risk due to interaction (RERI) of 1.59 (95% CI: 0.39– 3.19), an attributable proportion (AP) of 0.34 (95% CI: 0.08– 0.51), and a synergy index (SI) of 1.78 (95% CI: 1.13– 2.79). No statistically significant multiplicative interaction was found.Conclusion: CO and FHH may jointly contribute to hypertension in Chinese T2DM patients through an additive effect beyond their individual associations. Maintaining a healthy WC is especially important for T2DM patients with a family history of hypertension.Keywords: central obesity, hypertension, interaction, family history of hypertension, type 2 diabetes mellitus, waist circumference